Pertanggungjawaban Hukum Perbuatan Praktek Tukang Gigi - Ongkiwijaya, Imelda; Pasalbessy, John Dirk; Hehanussa, Deassy Jacomina Anthoneta (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The practice of dental artisans which is now increasingly mushrooming in the community seems to have caused serious problems, namely victims of practices that are not in accordance with procedures. Several cases indicate that it turns out that the practice of dental artisans has become one of the people's choices given the low cost and practicality in providing services, even though medically the consequences are often not considered, and if a victim arises, the legal issue is whether dental artisans can be held legally responsible, if so, what form? liability under civil law and criminal law, even according to health law itself. Purposes of the Research: The purpose of this article is to examine and anylize forms of legal protection for the victim in the practice of dental artisan. Methods of the Research: Answering the legal issues of this research, the research method using normative legal research is supported through a statutory approach, a concept approach and a case study approach. The sources of legal materials are primary, secondary and tertiary sources of legal materials collected through literature study and several documents which are then analyzed using qualitative analysis. Results of the Research: The results of the study concluded that judging from the health law and the law on the practice of medicine and dentistry, it is clear that the dentist profession is one of the academic professions that must be pursued through formal academic education in higher education so as to obtain a dental professional degree, while dental artisans also get education although not through formal education. Likewise with their professional practice, both dentists and dental artisans have a clear practice basis, namely the law on medical practice and the Regulation of the Minister of Health, where in these regulations it is emphasized that apart from permits as well as reporting and supervision carried out by the Health Office where dental artisans perform practice. It turns out that not a few dental artisan practices do not get a permit, even in practice there are many cases such as the installation of dental braces, cleaning and installation of teeth that are not up to standard, resulting in victims who, when viewed from the law on the health of the victim, need legal protection. One form of protection is legal liability, both according to civil law and according to criminal law.